Tangible Value Biodiversitas Herbal dan Meningkatkan Daya Saing Produk Herbal Indonesia dalam Menghadapi Masyarakat Ekonomi ASEAN 2015 - Eka Intan Kumala Putri; Amzul Rifin; . Novindra; Heny Kuswanti Daryanto; . Hastuti; Asti Istiqomah (Jurnal Ilmu Pertanian Indonesia, 2014)
Herbs are environmentally friendly commodities that slogan 'back to nature'. Herbal is a reliable commodityIndonesia because herbal raw material comes from Indonesia's abundant biodiversity. However, the currentIndonesian herbal faced a number of challenges to be able to compete with the herbs that come from foreigncountries. The existence of the Free Trade Agreement can be seen by the opening of the market to the entry ofIndonesian herbal products imported from Cina, India, Malaysia, and others. Economically, Indonesia's tradebalance deficit with export figures of herbal products continues to decline. That is, the existence of free tradeagreements is adversely affected by the low competitiveness of herbal products against imported products thatcirculate in Indonesia. In the midst of adversity free trade, in 2015 has agreed a free trade agreement between theASEAN countries (EAC). Will EAC able to lift Indonesian herbal products from the domestic market?.